Use of augmented reality, virtual reality and artificial intelligence in secondary education: a systematic review (2024)
The objective of this systematic review was to gather information regarding the implementation of Disruptive Technologies (DT) such as Augmented Reality (AR), Virtual Reality (VR) and Artificial Intelligence (AI) in secondary education. The methodology was based on the PRISMA Statement in the Scopus and Taylor & Francis databases 53 documents were retrieved using the established criteria. The findings focus on three aspects: Bibliometric analysis by year and country, implementation of AR, VR or AI and results obtained in the various fields of knowledge affected by DTs. Interventions with these technologies show a growing trend in the implementation of AR. The effectiveness of the implementation of AR, VR and AI generated cognitive, emotional, and teaching-learning process improvements. On the other hand, it is recommended to deepen the research on the implementation of these DTs and to integrate in the studies the combinations among technologies.